Collapsing ecosystem functions on an inshore coral reef. (1st July 2021) - Tebbett, Sterling B.; Morais, Renato A.; Goatley, Christopher H.R.; Bellwood, David R.
Abstract: Ecosystem functions underpin productivity and key services to humans, such as food provision. However, as the severity of environmental stressors intensifies, it is becoming increasingly unclear if, and to what extent, critical functions and services can be sustained. This issue is epitomised on coral reefs, an ecosystem at the forefront of environmental transitions. We provide a functional profile of a coral reef ecosystem, linking time-series data to quantified processes. The data reveal a prolonged collapse of ecosystem functions in this previously resilient system. The results suggest that sediment accumulation in algal turfs has led to a decline in resource yields to herbivorous fishes and a decrease in fish-based ecosystem functions, including a collapse of both fish biomass and productivity. Unfortunately, at present, algal turf sediment accumulation is rarely monitored nor managed in coral reef systems. Our examination of functions through time highlights the value of directly assessing functions, their potential vulnerability, and the capacity of algal turf sediments to overwhelm productive high-diversity coral reef ecosystems. Highlights: We quantified coral reef function-spaces that linked time-series data to processes. The herbivorous fish and algal turf communities shifted to low-productivity states. The productivity of the herbivorous fish assemblage declined by 50%. Changes appeared to be driven by a >2100% increase in algal turf sediment loads. Algal turf sediments are not monitored nor managed on nearly all coral reefs.